Productivity of Onions Using Subsurface Drip Irrigation versus Furrow Irrigation Systems with an Internet Based Irrigation Scheduling Program - Juan Enciso; John Jifon; Juan Anciso; Luis Ribera (International Journal of Agronomy)
Selection of the proper irrigation method will be advantageous to manage limited water supplies and increase crop profitability. The overall objective of this study was to evaluate the effect of subsurface drip irrigation (SDI) and furrow irrigation on onion yield and irrigation use efficiency. This study was conducted in two locations, a commercial field and a field located at the Texas A&M AgriLife Research Center in Weslaco, TX. This study was conducted as a split-plot design for both sites with two treatments (SDI and furrow irrigation) and three replications per treatment. The total onion yield obtained with the SDI systems was more than 93% higher than the yield obtained with furrow irrigation systems. The large onion size was 181% higher for the SDI system than the furrow system in both sites. The colossal size yield was also higher. At one site colossal yield was 206% higher than furrow, while at another site furrow yielded no colossal onions and SDI had some production. It was concluded that drip irrigation systems more than double yields and increased onion size while using almost half of the water. This was due to SDI allowing for more frequent and smaller irrigation depths with higher irrigation efficiency than furrow irrigation systems.